2012
DOI: 10.1097/rlu.0b013e318238f51a
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of F-18 FDG and C-11 Methionine PET/CT for the Evaluation of Recurrent Primary Brain Tumors

Abstract: MET should be the radiotracer of choice in the evaluation of recurrence of primary brain tumors because the sensitivity for detection and delineation of the possible recurrent tumor, as well as secondary deposits, is higher with MET. MET-PET is an easier technique to interpret, irrespective of the glioma grade, with less interobserver variability and straightforward localization of tumorous accumulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 20 publications
0
36
0
3
Order By: Relevance
“…11 C-Methionine positron emission tomography/computed tomography (Met-PET/CT) has been increasingly used in oncologic imaging as a complementary method to 18 F-FDG PET/CT that is limited in the differentiation of a malignant lesion from coexisting peritumoral or post-therapeutic inflammatory change [11][12][13]. In particular, it has been known that methionine is one of amino acids comprising parathyroid hormone and that it is closely related with biosynthesis of parathyroid hormone [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…11 C-Methionine positron emission tomography/computed tomography (Met-PET/CT) has been increasingly used in oncologic imaging as a complementary method to 18 F-FDG PET/CT that is limited in the differentiation of a malignant lesion from coexisting peritumoral or post-therapeutic inflammatory change [11][12][13]. In particular, it has been known that methionine is one of amino acids comprising parathyroid hormone and that it is closely related with biosynthesis of parathyroid hormone [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…These different criteria for visual assessment in 18 F-FDG studies may inevitably bring bias to our pooled data. Moreover, Tripathi et al 24 reported that even within the same 18 F-FDG study, interobserver agreement for visual interpretation was not good. The difficulty in discriminating the lesion and surrounding normal brain tissue in some patients and the subjectivity of visual assessment of the interpreter may together contribute to the low diagnostic ac- curacy and require us to explain the pooled results prudently when using qualitative evaluation in 18 F-FDG-PET.…”
Section: Discussionmentioning
confidence: 99%
“…We excluded each study in turn and checked how the new summary diagnostic values could be influenced by the removed one. We also performed direct comparison of the diagnostic values of 18 F-FDG and 11 C-MET PET from the 5 studies with the same population of the patients [22][23][24][25][26] to diminish the potential bias induced by pooling data from all the studies, though the data subset was smaller. Publication bias was tested by using the linear regression method and funnel plot of Deeks et al 40 A P value Ͻ .05 in this linear regression indicates potential publication bias.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations